The Literary Qizilbashes: (An Introduction to the Literary Activities and Cultural Approaches of High-Ranking Qizilbash Amirs during the Reign of Shah Tahmasp I of the Safavid Era) - Alı Abolghasemı; Nozhat Ahmadi; Aliakbar Jafari (تاریخ اسلام و ایران, 2024)
In the first decades of the emergence of the Safavid state—a period marked by conquest and consolidation—the military aristocracy of the Qizilbash played a dominant role within the power structure. However, following the stabilization of the state and the efforts of the political leadership to curtail the power of the Qizilbash military, there was a gradual change in the nature of the Qizilbash military class. As a result, some Qizilbash military figures distanced themselves from their purely martial role and traditional identity as warriors by engaging in administrative, literary, and artistic activities. Given the importance of this issue in Safavid studies, this study uses a descriptive-analytical approach to reflect on the military structure of the Qizilbash and examines the tension between the "men of the sword" and the "men of the pen." The aim is to explore and explain the literary activities and cultural approaches of the high-ranking Qizilbash amirs during the reign of Shah Tahmasp. Specifically, it addresses the question: What factors contributed to the change in the position and function of some Qizilbash military aristocrats and their literary and cultural activities??The findings of the study indicate that several factors paved the way for this change: the policy of limiting the Qizilbash’s power, Shah Tahmasp's religious and educational policies, personal interests and inclinations, early childhood education and training, previous administrative and governmental experience of some Qizilbash tribal leaders (oymaq leaders), favorable economic conditions, and cultural influences stemming from life and upbringing in cities and regions with a rich cultural and economic heritage. These factors together facilitated the integration of some Qizilbash warriors into the ranks of literati and poets.